If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(a + -3) = 40 Reorder the terms: 2(-3 + a) = 40 (-3 * 2 + a * 2) = 40 (-6 + 2a) = 40 Solving -6 + 2a = 40 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 2a = 40 + 6 Combine like terms: -6 + 6 = 0 0 + 2a = 40 + 6 2a = 40 + 6 Combine like terms: 40 + 6 = 46 2a = 46 Divide each side by '2'. a = 23 Simplifying a = 23
| 0.34=lnx | | 6x-1=125 | | 2+x+3x=34 | | y=x(x-2y)+2y(x+2y) | | -4x^2+11x-6=o | | (x^2)-x+20=0 | | 16q-18=qr+t | | 5x+6-x=-30 | | 0.5x+7=-9 | | G-24=14 | | x^3-12x^2+230.4=0 | | 25+4y=25+16 | | 5x-3(x-3)=4+5x-8 | | 0.5x+6=17 | | -4(6x-7)=-24x-28 | | -12x-65=-7x | | 5-(2x+2)=-(-3x+5)-x | | 3(-2x+5)=9 | | 1x+.5y=6 | | 21=7y+7+(y+3) | | 7(-6x+1)=-329 | | X-2(x+3)=-2(x+1)-4 | | 2x+1+3x=30 | | x=a(a-b)+b(a+b) | | x=-3+13 | | 2x-3+19=17 | | 5x=63.25 | | [2x+3]=-5 | | 7(-1x+5)=-7 | | x^2-2+3x+8=180 | | -8y=48-4y | | 7.1x+4.4-2x-8.7= |